Potential Recurrence of Odontogenic Keratocyst Post-Surgery, Rapid Review - Widyandhika, Cindy Widyandhika Ayu; Anggraini, Jamas Ari; Yusuf, Harmas Yazid (Dentistry Faculty, 2023)
Background: Odontogenic keratocyst is one of the most frequent cysts found in the jaw. Odontogenic keratocyst, or OKC, is a benign but locally aggressive cyst with a higher recurrence rate than other odontogenic cysts after surgical treatment. The OKC recurrence rate is reported to be around 2.5% to 62.5%. Objective: This rapid review analyzes the most frequent recurrence potential factors after surgical procedures. Material and Methods: Articles search by using a combination of the keywords